2020
DOI: 10.3389/fmed.2020.00510
|View full text |Cite
|
Sign up to set email alerts
|

Topical Melatonin Improves Gastric Microcirculatory Oxygenation During Hemorrhagic Shock in Dogs but Does Not Alter Barrier Integrity of Caco-2 Monolayers

Abstract: Systemic administration of melatonin exerts tissue protective effects in the context of hemorrhagic shock. Intravenous application of melatonin prior to hemorrhage improves gastric microcirculatory perfusion and maintains intestinal barrier function in dogs. The aim of the present study was to analyze the effects of a topical mucosal melatonin application on gastric microcirculation during hemorrhagic shock in vivo and on mucosal barrier function in vitro . In a ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…In the same trial nitroglycerin improved intestinal barrier function ( 17 ). Likewise, local application of melatonin ( 18 ) and losartan ( 19 ) were able to ameliorate the decrease of gastric mucosal oxygenation in a state of acute hemorrhage. Systemic hypercapnia and hyperoxia proved to exert favorable effects in the context of hemorrhagic shock ( 11 , 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the same trial nitroglycerin improved intestinal barrier function ( 17 ). Likewise, local application of melatonin ( 18 ) and losartan ( 19 ) were able to ameliorate the decrease of gastric mucosal oxygenation in a state of acute hemorrhage. Systemic hypercapnia and hyperoxia proved to exert favorable effects in the context of hemorrhagic shock ( 11 , 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Only MFI improved in the late course of hemorrhagic shock indicating favorable properties of carbachol on oral microcirculation. However, results from oral microcirculatory measurements cannot be transferred doubtless to other parts of the gastrointestinal tract, since our group could identify a different response of the oral and gastric microcirculation to topical melatonin treatment (36) and hypothermia (34) in a similar canine model of hemorrhagic shock. The observation that carbachol improves gastric but not oral oxygenation might indicate that during hemorrhage there is a more pronounced sympathetic activation in the oral region whereas the gastric region can still be modulated.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, drugs were applicated locally to avoid systemic side effects. In the past, our group used various local treatment regimens to improve gastric tissue oxygenation ( 34 36 ). None of those trials revealed systemic complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, many investigators choose a corresponding shock model to test if a therapeutic intervention results in a survival advantage ( 23 , 24 ). More moderate shock states are used when the focus is not on survival rates, but, e.g., on repetitive measurements in individual animals ( 25 27 ). As stated above, also the shock duration can be adjusted ( 28 ).…”
Section: Animal Disease Models To Study Hemorrhagic and Septic Shockmentioning
confidence: 99%